2020
DOI: 10.1002/ijgo.13126
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus prevalence and distribution in self‐collected samples from female university students in Maputo

Abstract: Objective: To characterize human papillomavirus (HPV) prevalence and distribution among female university students in Maputo, Mozambique, and evaluate the determinants of HPV infection. Methods:A cross-sectional study among 504 female university students between February and April 2017. Cervicovaginal self-collected samples were analyzed for HPV genotypes by polymerase chain reaction-restriction fragment length polymorphism and Anyplex TM II HPV28 Detection kit (Seegene ® ). Results:The prevalence of any HPV g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
0
8
1
1
Order By: Relevance
“…One study also found a higher prevalence among WLHIV (26% HIV-positive, 12% HIV-negative) [ 15 ]. However, both found lower prevalences than this study [ 15 , 19 ]. The higher prevalence in this study may be due to geographic variability, differences in HPV specimen collection, or differences in HPV assay sensitivity.…”
Section: Discussioncontrasting
confidence: 87%
“…One study also found a higher prevalence among WLHIV (26% HIV-positive, 12% HIV-negative) [ 15 ]. However, both found lower prevalences than this study [ 15 , 19 ]. The higher prevalence in this study may be due to geographic variability, differences in HPV specimen collection, or differences in HPV assay sensitivity.…”
Section: Discussioncontrasting
confidence: 87%
“…HPV66 was recently reported to also have a high prevalence in low-grade cervical lesions of women from Mexico City (45.7%); the prevalence was lower in CC samples (3.6%), although they used a different detection method (INNO-LiPA) [ 52 ]. HPV66 has also been frequently found in Chile [ 53 ], Africa [ 54 , 55 ] and China [ 56 ], among others.…”
Section: Discussionmentioning
confidence: 99%
“…In a study published in 2004 on cervical cancer in Mozambique the dominant HPV types were 16 and 18, being present in 69% of tumours [38]. In a later study published in 2011 on HPV types in cervical cancers in Mozambique HPV 16 and 18 were the most common types detected in cervical cancer biopsies (among both HIV-negative and HIV-positive women) [39,40].…”
Section: Discussionmentioning
confidence: 99%